Targeting lipid metabolic reprogramming to alleviate diabetic kidney disease: molecular insights and therapeutic strategies - Yu, Wei; Haoyu, Yang; Ling, Zhou; Xing, Hang; Pengfei, Xie; Anzhu, Wang; Lili, Zhang; Linhua, Zhao (Frontiers in Immunology, 2025)
Diabetic kidney disease (DKD) is one of the major complications of diabetes, and its pathological progression is closely associated with lipid metabolic reprogramming. Under diabetic conditions, renal cells undergo significant lipid metabolic abnormalities, including increased lipid uptake, impaired fatty acid oxidation, disrupted cholesterol efflux, and enhanced lipid catabolism, as adaptive responses to metabolic stress. These changes result in the accumulation of lipids such as free fatty acids, diacylglycerol, and ceramides, leading to lipotoxicity that triggers inflammation and fibrosis. Hypoxia in the DKD microenvironment suppresses fatty acid oxidation and promotes lipid synthesis through the HIF-1α pathway, while chronic inflammation exacerbates lipid metabolic disturbances via inflammatory cytokines, inflammasomes, and macrophage polarization. Targeting lipid metabolism represents a promising therapeutic strategy for alleviating DKD; however, further clinical translational studies are warranted to validate the efficacy and safety of these approaches.